STRESS-STRAIN STATE OF ROCKS OF STRUCTURALLY HETEROGENEOUS DEPOSITS IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Laboratory tests are widely used in the study of the stress state of an array. However, these tests are not enough, and at the research stage the authors propose a method for multi-parameter control of the properties and stress-strain state of rocks.
Keywords: structural heterogeneity, rock properties, ore deposits, stress-strain state